If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/2(y-2)+2=3/8(3y-4)
We simplify the equation to the form, which is simple to understand
1/2(y-2)+2=3/8(3y-4)
Simplifying:
+ 0.5*(y-2)+2=3/8*(3y-4)
Simplifying:
+ 0.5*(y-2)+2=0.375*(3y-4)
Reorder the terms in parentheses
+( + 0.5y-1)+2=0.375*(3y-4)
Remove unnecessary parentheses
+ 0.5y-1+2=0.375+*(+3y-4+)
Reorder the terms in parentheses
+ 0.5y-1+2=+(+1.125y-1.5)
Remove unnecessary parentheses
+ 0.5y-1+2=+1.125y-1.5
We move all terms containing y to the left and all other terms to the right.
+ 0.5y-1.125y=-1.5+1-2
We simplify left and right side of the equation.
-0.625y=-2.5
We divide both sides of the equation by -0.625 to get y.
y=4
| n+16=8(n+9) | | 36-4d=4(9-2d) | | -9=w+5 | | 9x-5y=7 | | 56+8x=80+12x | | 12(2x-3)=(8x+5) | | -8(x+8)=-120 | | 5.2+1.6x=2.6x | | -4(2p+2)-32=3(5p+2) | | 14-[2q+5]=-2q+9 | | 7+19t-1=7t+38-4t | | -3n+7(7n+7)=371 | | v+f-2=2 | | 4/5-2/3= | | 5y-5+y+41=8y+40-6y | | 40+2x+8=6 | | m+20=1 | | 8s-16s=24 | | 2r+13r=120 | | -4r-3(8+4r)=-88 | | 18s-16s=24 | | -5(w-4)=-2w-7 | | (-14)+x=10 | | 5v-29=8(v-4) | | -29x+29x=2 | | 114=46 | | 2x-3y-14=0 | | 5y=2(y-3) | | 8+5n-3=9n+13-6n | | -4+12=4b-1-3b | | -7.3x=43.8 | | 37x+17=6(6x+17) |